The Effect of Word Card Media on the Ability to Write Effective Sentences in Class III Indonesian Language Subjects at SD Negeri Nyantong - Sunanih; Yopa Taufik Saleh; Septia Septiani Awaliya (LPPM Universitas Buana Perjungan Karawang, 2021)
The purpose of this study was to examine the effect of word card media on students' writing ability in learning Indonesian for grade 3 SD Negeri Nyantong. This study used an experimental method. This research design was Quasi Experimental Design with Nonequivalent Control Group Design. The study population was 35 respondents and the experimental class sample was 17 people, and the control class was 18 people. Sampling with purposive sampling. Collecting data through interview sheets, tests and documentation. Quantitative data processing is completed through data processing with hypothesis testing. The results of research on students' writing skills in Indonesian subjects using word card media showed differences and increases in the average writing ability of students before and after treatment. With a significance value of 0, 000 <0.05, so the hypothesis is accepted. So it can be concluded that the word card media is effective and influences the writing ability of students in learning Indonesian for grade 3 SD Negeri Nyantong.